The Effect of Verapamil on Skeletal Muscle Contractile Responses in Rats - Apisariyakul, Amphawan; Satrabhaya, Suriya (Journal of Basic and Applied Pharmacology, 2015)
Verapamil at the concentrations ranging from 0.01-0.08 mM produced a dose-related twitch depression in isolated rat phrenic nerve-hemidiaphragm preparations. The maximum effective concentration was 0.05 mM which produced 76 percent depression. Neurally evoked twitch was affected more significantly than directly evoked one. Verapamil at a concentration of 0.04 mM significantly synergized the in vitro neuromuscular blocking effect of pancuronium (0.001 mM) and of succinylcholine (0.001 mM). Verapamil (0.05 mM) inhibited twitch potentiation produced by 2.6 mM caffeine in curarized rat diaphragm preparations. This drug also abolished acetylcholine-induced contracture in denervated rat gastrocnemius preparations. It was also found that calcium exerts only a partial antagonistic effect on the neuromuscular blockade produced by verapamil in vitro. The effects of verapamil on skeletal muscle contractile responses in rats and its possible sites of action are discussed.